A Thermoelectric Zintl Phase Na2+xGa2+xSn4–x with Disordered Na Atoms in Helical Tunnels. (14th July 2015) - Yamada, Takahiro; Yamane, Hisanori; Nagai, Hideaki
<x xml:space="preserve">Abstract</x> A polycrystalline sample of Na2+xGa2+xSn4–x with x = 0.19 has low thermal conductivities of 0.56 and 0.58 W m−1 K−1 due to static and dynamic positional disorder of Na atoms in the crystal structure and dimensionless figures of merit (ZT values) values of 0.98 and 1.28 at 295 and 340 K, respectively. The performance is comparable to those of commercial Bi2Te3‐based materials.